THE IMPACT OF QURAN-BASED MATHEMATICS TEACHING ON MATHEMATICAL CONCEPT UNDERSTANDING AMONG STUDENTS AT MI DARUL QUR'AN AL HASAN NW PERESAK - Zohri Ratna (Formad English Foundation NTB Jakarta, 2024)
This study investigates the impact of Qur'an-based mathematics instruction on conceptual understanding among fourth-grade students at MI Darul Qur'an Al Hasan NW Peresak. Addressing a gap in the literature, the research evaluates how integrating Qur'anic values into mathematics teaching affects student comprehension and engagement. A quasi-experimental design was employed, involving 15 students randomly assigned to an experimental group (n=8) and a control group (n=7). The experimental group received Qur'an-based mathematics instruction, while the control group followed conventional methods. Pre-test and post-test scores were collected to measure changes in understanding, and statistical analysis was conducted using a t-test. The results indicate that the experimental group significantly improved their average post-test scores from 65 to 85, compared to a modest increase from 64 to 70 in the control group. The t-test revealed a t-value of 4.25, exceeding the critical t-value of 2.14, confirming a statistically significant difference. Qualitative data from interviews and classroom observations revealed enhanced student motivation and engagement in the experimental group, as they found the Qur'an-based approach more relevant and engaging. These findings suggest that integrating religious values into the curriculum can significantly improve conceptual understanding and student motivation in mathematics. The study highlights the potential of Qur'an-based teaching methods in enhancing educational outcomes and provides a basis for implementing similar approaches in other educational contexts.